435 Renal denervation in a patient with uncontrolled arterial hypertension secondary to polycystic kidney disease. (8th December 2021) - Widmann, Maddalena; Fezzi, Simone; Castaldi, Gianluca; Tavella, Domenico; Pighi, Michele; Ribichini, Flavio Luciano
Abstract: Aims: Autosomal dominant polycystic kidney disease (ADPKD) represents the most common inherited cause of chronic kidney disease. Typical manifestations of this condition include secondary hypertension, abdominal pain, haematuria and urinary tract infections. Despite the progressive increase in the use of antihypertensive therapy in patients with ADPKD in the last decades, reaching blood pressure target is often difficult in this setting due to the complex physiopathology of arterial hypertension in ADPKD. Catheter-based renal sympathetic denervation (RDN) represents nowadays a therapeutic strategy to approach resistant hypertension. Based on consistent results of several sham-controlled clinical trials, the evidence of safety and efficacy of this procedure is increasing, also in patients with multiple comorbidities including chronic kidney disease. Patients with ADPKD often develop chronic severe kidney-related pain, caused by distension of the renal capsule due to the expansion of the cysts. RDN was proposed to be an effective therapeutic option able to relieve loin pain. Methods: A 49-year-old man affected by ADPKD was referred to our centre for resistant uncontrolled arterial hypertension, despite combined therapy with five antihypertensive drugs. He also complained about intense loin pain and 3 years earlier underwent two surgical interventions to remove voluminous renal cysts, that did not relieve chronic pain. His kidney function was moderately decreased at presentation, with progressive decline in the previous years. After a multi-disciplinary discussion with a nephrologist and algologist, the patient was proposed for RDN with the aim of lowering blood pressure and reducing pain. He was treated in July 2018, and after the procedure, was observed a better control of blood pressure but no benefits on pain. Because of the persistence of intractable loin pain, the patient was submitted to a second RDN in December 2018. Also, after this procedure, blood pressure declined remarkably, decreasing his need for antihypertensive medications without a significant worsening of kidney function. Unfortunately, no benefit on chronic pain was observed. Results: ADPKD is characterized by the progressive bilateral development of focal renal cysts. Cardiovascular complications, mainly related to hypertension, are a major cause of morbidity and mortality for these patients. RDN could be a valid and safe therapeutic option for the treatment of secondary hypertension in this setting.